Assessing the Validity and Reliability of the Adapted Staff Stressors Scale in Chinese Universities - Tang, Yi-xuan; Ling, Ying-Leh (South Asian Journal of Social Sciences and Humanities, 2025)
The purpose of this study was to develop and validate a stressors scale with reflective and  formative indicators for teaching staff in Ningxia, China. The scale was analyzed through a  questionnaire survey of 237 staff members using exploratory factor analysis (EFA) and  validation factor analysis (CFA). The results showed that the scale had good structural  validity and internal consistency, and the exploratory factor analysis extracted six dimensions  explaining 66.908% of the variance. The Cronbach's alpha coefficient and the combined  credibility were within the acceptable range. Further validation factor analysis showed that  validity assessments (including convergent and discriminant validity) confirmed the  robustness of the scale. For formative indicators metrics such as Variance Inflation Factor  (VIF) were used to check for covariance between indicators to avoid redundancy. In addition,  the importance and weights of the indicators were analyzed to confirm their relative  importance in defining the structure. In summary, the Staff Stressors Scale can be used to  measure faculty stress in private institutions in the Ningxia region of China, and it can also  provide a basis for further research in the future.
Keywords: Reliability; validity; staff stressors scale; private HEIs; staff stress